Augmented reality and problem-based learning as a strategy that living labs support [La realidad aumentada y el aprendizaje basado en problemas como estrategia que soportan los living lab] (2020)
The accelerated changes that the uses of information technologies (IT) have provoked in different social, political, economic, and cultural scenarios in the global sphere have led to an investigation and questioning in such an important area as education, on how to use IT-supported educational models and strategies for the benefit of educational scenarios and their actors. To answer these concerns, the aim of this article is to make a state of the art on: augmented reality (AR), living labs and active learning strategies that accompany educational initiatives supported by IT, the methodology used to make the state of the art on the subject is the systematic review of literature and additional tools of analysis were used as it was the tree of science. The results obtained show that IT is in exponential use as a support in the current teaching-learning scenarios and their actors. Most of the research carried out in AR applied to education has concentrated on identifying the benefits of AR in science education, ecology, field trips, mathematics and geometry, scientific studies and in general activities where students can observe elements that could not be visualized in the real world without the use of a specialized device. The results in the tests of living laboratories or Living Labs equipped with AR technology showed as positive that both theory and practice can be combined so that students can associate abstract content with real situations when learning, through electronic devices that explain the actions to be executed and have clarity of the desired objective. And finally, some authors mention that the teaching-learning process has been focused on the development of games through problem-based learning methodologies or ABP, structured in role-playing allowing the realization of participatory simulations of co-creation and developing collaborative learning strategies. © 2020, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.